Risk Factors Foranemia in Pregnant Women in Konawe Islands Regency - Malaiji, Endang Fitriyani; Tasnim, Tasnim; Amraeni, Yunita (Waluya The International Science of Health Journal, 2023)
Background: The prevalence rate of anemia incidence in pregnant women in Konawe Kepulauan Regency in 201was 9, namely 72.9%, in 2020 it was 69.7% while the prevalence of pregnant women who received 90 Fe tablets in the year 2018 was 49.5%, in 2019 it was 61.25% and 62.7% (Konawe Islands District Health Office 201 8-2021). The purpose of the study was to analyze the risk factors for the incidence of anemia in pregnant women in Konawe Islands Regency. Methods: This study used the Case Control Study approach. The control population was 106 respondents and the control population was 562 respondents. The Research Sample totaled 47 case samples and 47 control samples. The Sample Technique in this study is the Cluster Random Sampling Technique. The data is processed using the Odds Ratio Test. Result: The results showed that education OR 2,424 LL value 0.876 UL value 6.707 and Φ 0.179, family income OR 57,400 LL value 16.242 UL value 202.849 and Φ 0.766, role of midwife OR 2,343 LL value 1,823 value UL 3.011 and Φ 0.383, anemia in pregnant women in konawe district island Conclusion: The conclusions in this study show that education and family income, midwife role are risk factors for anemia in pregnant women in Konawe Islands Regency. It is hoped that the Health Office and Puskesmas will always provide education in the form of counseling and counseling related to maternal and child health to reduce the incidence of anemia in pregnant women.